Idea sprawiedliwości społecznej w kontekście procesu globalizacji - Kowalczyk, ks. Stanisław (Annales. Etyka w Życiu Gospodarczym, 2008)
The subject of social justice are groups or whole societies – also states, object of this justice are their mutual rights and common good. The process of economic and technological globalization means among other things: establishment of the world market, predominant role of international companies, centralization of leading elites’ decisions, financial disproportion between individual people and countries. In the teaching of contemporary popes (John XXIII’s, Paul VI’s, John Paul II’s) the idea of social justice has also international dimension and therefore process of economic globalization ought to respect two principles of the Church’s social teaching: the principle of the subsidiarity and the principle of solidarity. The principle of the subsidiarity demands to respect subjectivity of all nations and states as well as to aid their integral development. The principle of solidarity postulates creation of common good of world society, this good are: peace, economic prosperity, commerce profitable for all states, cooperation and financial help of rich countries for underdeveloped countries. The social justice in the international dimension is the expression and the imperative of solidarity of all nations and states.